2019
DOI: 10.1002/jbmr.3942
|View full text |Cite
|
Sign up to set email alerts
|

LIGHT/TNFSF14 Promotes Osteolytic Bone Metastases in Non-small Cell Lung Cancer Patients

Abstract: Tumor necrosis factor superfamily member 14 (TNFSF14), LIGHT, is a component of the cytokine network that regulates innate and adaptive immune responses, which promote homeostasis of lymphoid organs, liver, and bone. Metastatic tumors often disrupt the tissue microenvironment, thus altering the homeostasis of the invaded organ; however, the underlying mechanisms required further studies. We investigated the role of LIGHT in osteolytic bone disease induced by metastatic non‐small cell lung cancer (NSCLC). Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Osteoclasts, the only cells capable of bone resorption, derived from myeloid lineage, were reported to be controlled by RANKL, PTHrP and Jagged 1 61‐64 . In a recent report, LIGHT (tumour necrosis factor superfamily member 14, TNFSF14), derived from monocytes, was shown to promote osteolysis in NSCLC bone metastases and could be a new therapy target 65 . RANKL can be secreted by osteoblast lineages or stromal cells, and PTHrp can be derived from tumour cells 61,66‐68 .…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts, the only cells capable of bone resorption, derived from myeloid lineage, were reported to be controlled by RANKL, PTHrP and Jagged 1 61‐64 . In a recent report, LIGHT (tumour necrosis factor superfamily member 14, TNFSF14), derived from monocytes, was shown to promote osteolysis in NSCLC bone metastases and could be a new therapy target 65 . RANKL can be secreted by osteoblast lineages or stromal cells, and PTHrp can be derived from tumour cells 61,66‐68 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, here we also demonstrated LIGHT involvement in the spontaneous osteoclastogenesis, in vitro, in PBMC of obese patients. Consistently, LIGHT is a pro-osteoclastogenic cytokine [ 21 ] and high levels have been demonstrated in erosive bone disease, firstly in rheumatoid arthritis [ 48 ] and then by bone metastatic non-small cell lung cancer (NSCLC), in osteolytic multiple myeloma, alkaptonuria, chronic kidney disease (CKD), hemodialysis patients, and post-menopausal osteoporosis [ 19 , 21 , 22 , 23 , 24 , 25 ]. In these different diseases with bone involvement, the elevated LIGHT levels are primarily correlated to its pro-osteoclastogenic role, as we and other authors have reported [ 21 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, many pro-inflammatory cytokines involved in obesity are also crucial mediators of osteoclastogenesis, with consequent increase of bone resorption activity [ 18 ], and thus supporting the link between obesity and altered bone turnover. One of these cytokines could be represented by LIGHT (homologous to Lymphotoxins exhibiting Inducible expression and competing with herpes simplex virus Glycoprotein D for herpes virus entry mediator (HVEM), a receptor expressed by T lymphocytes) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. LIGHT/TNFSF14 is member of TNF superfamily and it is a key cytokine of the TNF-lymphotoxin network [ 27 , 28 , 29 ], expressed by immune cells, with a key role as a co-stimulatory molecule [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Edwards et al first demonstrated in rheumatoid arthritis that LIGHT (a co-stimulatory molecule) is involved in erosive bone disease [8]. We then deepened the understanding of LIGHT's role in bone remodeling in the pathologies of multiple myeloma, lung cancer, CKD, and alkaptonuria [9,[11][12][13]29]. In 2018, we studied the bone phenotype of Tnfsf14 −/− mice and demonstrated trabecular bone loss, suggesting that a physiological basal concentration of LIGHT is required to maintain physiological bone remodeling [10].…”
Section: Discussionmentioning
confidence: 99%